Relationship between particulate matter and population of airborne microorganism in goat farm: a case study at Ladang Pasir Akar, Terengganu - Azman Azid (Tanjung Malim, 2021)
Relationship between particulate matter and population of airborne microorganism in goat farm: a case study at Ladang Pasir Akar, Terengganu by Azman Azid